Cambridge primary Mathemathics : Learner's book 5 - Wood, Mary; Low, Emma (United Kingdom : Cambridge University Press, 2021)
Whether they are presenting data in a range of formats or exploring cube numbers Cambridge Primary Mathematics help your learner's develop their mathematiccal thinking skills, They will be fully supported with worked examples and plenty of pratice exercises, while projects throughout the book provide opportunities for deeper investigation of mathematical concept - including predicting patterns using matchsticks.
Keywords: Mathematics -- Prediction Patterns